INFLUENCE OF THE PEDAGOGICAL GAME ON THE FORMATION OF THE PROFESSIONALLY-ORIENTED PERSONALITY OF THE FUTURE TEACHER - Козак, Н.Д.; Обміняна, Г.Л.; Яценко, Т.В. (Modern engineering and innovative technologies, 2024)
The article highlights the main ideas of collective creativity of students. Reveals the effect of educational games on the formation of professionally oriented personality. Pointed out in types of games and their features. The role of play in the formatio